Effect of cyproterone acetate on adrenocortical function in children with precocious puberty. Issue 3 (March 1981) - Savage, D C; Swift, P G
Abstract : Seven children with precocious puberty were treated with cyproterone acetate and their adrenal function studied. In each child the drug caused significant adrenal hypofunction which was secondary to adrenocorticotrophic hormone suppression. None of these children had clinical evidence of adrenal hypofunction and it is assumed that the drug has glucocorticoid-like properties. Children receiving cyproterone acetate should carry information to warn doctors of this effect since they may require steroid cover during illness.